Kemampuan Guru Bahasa Jawa SMP Negeri 1 Kedungtuban Blora Mengintegrasikan 4 C dalam RPP Semester Gasal Tahun 2020/2021 - Prameswari, Elfa Mahendra; Sulanjari, Bambang; Alfiah, Alfiah (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2022)
The purpose of this study was to determine the ability of Javanese language teachers at SMP Negeri 1 Kedungtuban Blora in integrating 4C elements (communication, Collaboration, Critical thinking, and Creativity) in the Learning Implementation Plan (RPP). This research uses a descriptive method. The data of this research are RPP grade VII, VIII, and IX odd semesters of Javanese language teachers at SMP Negeri 1 Kedungtuban Blora which were collected using documentation techniques. After the data is collected, data analysis techniques are carried out using interactive models, including reducing data, displaying data, and drawing conclusions. The results of this study illustrate the ability of the teacher to integrate the 4C elements that are observed through the development of indicators. From the 4C elements that are observed through the indicators of the Collaboration element, Critical thinking, Creativity is present in each RPP. Meanwhile, the element of communication is only found in four lesson plans from the six lesson plans analyzed.